PENGARUH KUALITAS PELAYANAN, KUALITAS MAKANAN DAN HARGA TERHADAP KEPUASAN - Herlina Sofiah; Sri Ekowati ((JEMS) Jurnal Entrepreneur dan Manajemen Sains, 2021)
This study aims to determine the effect of service quality, food quality and price on customer satisfaction at Warung Nasi Uduk Didi Bengkulu, either partially or simultaneously. There are several factors that will be discussed in this study, including Service Quality (X1), Food Quality (X2) and Price (X3). The object of this research is the customers of Warung Nasi Uduk Didi Bengkulu, amounting to 110 people. In this research, the writer uses the method of data collection by means of observation, distributing questionnaires and interviews.               There are several data analysis techniques used in this study, including by using instrument test, classical assumption test, respondent analysis analysis, multiple linear regression analysis, determinant coefficient, and hypothesis testing. From the results of the tests that have been done, it can be concluded that the variables of Service Quality (X1), Food Quality (X2) and Price (X3) have a partial or simultaneous effect on customer satisfaction at Warung Nasi Uduk Didi Bengkulu. From the results of multiple linear regression tests, the regression equation is obtained as follows: Y = 3.707 + 0.304 (X_1) + 0.226 (X2) + 0.274 (X3). Keywords: Service Quality, Food Quality, Price and Customer Satisfaction.